Doxorubicin-induced cardiotoxicity is mediated by neutrophils through release of neutrophil elastase - Bhagat, Anchit; Shrestha, Pradeep; Jeyabal, Prince; Peng, Zhanglong; Watowich, Stephanie S.; Kleinerman, Eugenie S. (Frontiers in Oncology, 2022)
The mechanisms by which Doxorubicin (Dox) causes acute and late cardiotoxicity are not completely understood. One understudied area is the innate immune response, and in particular the role of neutrophils in Dox-induced cardiotoxicity. Here, using echocardiography, flow cytometry and immunofluorescence staining, we demonstrated increased infiltration of neutrophils that correlated with decreased heart function, disruption of vascular structures and increased collagen deposition in the heart after Dox treatment. Depleting neutrophils protected the heart from Dox-induced cardiotoxicity and changes in vascular structure. Furthermore, our data using neutrophil elastase (NE) knock-out mice and the NE inhibitor AZD9668 suggest that neutrophils cause this damage by releasing NE and that inhibiting NE can prevent Dox-induced cardiotoxicity. This work shows the role of neutrophils and NE in Doxorubicin-induced cardiotoxicity for the first time and suggests a new possible therapeutic intervention.